2008
DOI: 10.1158/1078-0432.ccr-07-1842
|View full text |Cite
|
Sign up to set email alerts
|

Human High Molecular Weight–Melanoma-Associated Antigen: Utility for Detection of Metastatic Melanoma in Sentinel Lymph Nodes

Abstract: Purpose: Detection of micrometastasis in melanoma-draining lymph nodes is important for staging and prognosis. Immunohistochemical staining (IHC) using S-100p-HMB-45^, and MART-1^specfic antibodies is used for detecting metastases in sentinel lymph nodes (SLN). However, improvement in IHC is needed for melanoma micrometastasis detection. Experimental Design: Paraffin-embedded archival tissue (PEAT) specimens were obtained from 42 non-SLN macrometastases, 42 SLN metastases, and 16 tumor-negative SLNs of 100 mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…34,35 Goto et al has shown that immunohistochemical detection using HMW-MAAspecific antibodies were more sensitive and specific than the antibodies MART-1, S100p, and HMB-45 which are commonly used for detection of malignant melanoma metastases in sentinel lymph nodes. 36 In this study, we developed a DTIC resistant cell line, FEMX-200DR, from the sensitive cell line FEMX to examine whether induced DTIC resistance also is a determining factor for the effectiveness of 9.2.27PE. The induced DTIC resistance resulted in a higher resistance level to apoptosis in the FEMX-200DR cells, as higher concentrations of the apoptotic inducer STS was needed to obtain IC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Goto et al has shown that immunohistochemical detection using HMW-MAAspecific antibodies were more sensitive and specific than the antibodies MART-1, S100p, and HMB-45 which are commonly used for detection of malignant melanoma metastases in sentinel lymph nodes. 36 In this study, we developed a DTIC resistant cell line, FEMX-200DR, from the sensitive cell line FEMX to examine whether induced DTIC resistance also is a determining factor for the effectiveness of 9.2.27PE. The induced DTIC resistance resulted in a higher resistance level to apoptosis in the FEMX-200DR cells, as higher concentrations of the apoptotic inducer STS was needed to obtain IC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded tissue microarrays (TMA) for AJCC stage IV melanoma established at JWCI included 262 stage IV metastatic tumors with paired stage III tumor tissues, each in duplicate, from 137 patients (28,29). TMA also contained seven normal tissues with limited or no proliferation (adrenal gland, brain, kidney, and liver), in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…TMA also contained seven normal tissues with limited or no proliferation (adrenal gland, brain, kidney, and liver), in duplicate. TMA were clinically well-annotated with greater than 5 years follow-up (28,29). Immunohistochemistry (IHC) was performed as previously described (28,29), using the following Abs: mouse anti-human KPC1 Ab (1:50 dilution, #ab57549; Abcam), rabbit anti-human NF-κB1 p50 Ab (1:200 dilution, #sc-114; Santa Cruz Biotechnology), or mouse anti-human p27 Ab (1:100 dilution, #610241; BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…mAb were purified from ascitic fluid by sequential precipitation with ammonium sulphate and caprylic acid (24). The purity and activity of mAb preparations were assessed by SDS-PAGE analysis, and by testing with CSPG4-bearing melanoma cells in a binding assay.…”
Section: Methodsmentioning
confidence: 99%